Allosteric activation of sodium–calcium exchange by picomolar concentrations of cadmium - Dinh Le, Hoa (Blackwell Science Inc, 2005)
Chinese hamster ovary cells expressing the bovine cardiac Na(+)–Ca(2+) exchanger (NCX1.1) accumulated Cd(2+) after a lag period of several tens of seconds. The lag period reflects the progressive allosteric activation of exchange activity by Cd(2+) as it accumulates within the cytosol. The lag period was greatly reduced in cells expressing a mutant exchanger, Δ(241-680), that does not require allosteric activation by Ca(2+) for activity. Non-transfected cells did not show Cd(2+) uptake under the same conditions. In cells expressing NCX1.1, the lag period was nearly abolished following an elevation of the cytosolic Ca(2+) concentration. Cytosolic Cd(2+) concentrations estimated at 0.5–2 pm markedly stimulated the subsequent uptake of Ca(2+) by Na(+)–Ca(2+) exchange. Outward exchange currents in membrane patches from Xenopus oocytes expressing the canine NCX1.1 were rapidly and reversibly stimulated by 3 pm Cd(2+) applied at the cytosolic membrane surface. Exchange currents activated by 3 pm Cd(2+) were 40% smaller than currents activated by 1 μm cytosolic Ca(2+). Current amplitudes declined by 30% and the rate of current development fell sharply upon repetitive applications of Na(+) in the presence of 3 pm Cd(2+). Cd(2+) mimicked the anomalous inhibitory effects of Ca(2+) on outward exchange currents generated by the Drosophila exchanger CALX1.1. We conclude that the regulatory sites responsible for allosteric Ca(2+) activation bind Cd(2+) with high affinity and that Cd(2+) mimics the regulatory effects of Ca(2+) at concentrations 5 orders of magnitude lower than Ca(2+).